EVALUASI TINGKAT RESPONSIVITAS MASYARAKAT KAMPUNG HERBAL TERHADAP RUANG TERBUKA HIJAU DI NGINDEN SURABAYA - Theresia Evelyn Ratoe; Amirul Mustofa; Eny Haryati (Journal Publicuho, 2023)
This study aims to evaluate the level of responsiveness of green open spaces in the city of Surabaya, with a focus on the case study of Nginden Herbal Village, Surabaya. The research method used is descriptive with a qualitative approach. Research data were obtained through questionnaires to the herbal village community and interviews with related village officials. The results of the questionnaire show that the majority of people are satisfied with accessibility, availability of facilities, and environmental sustainability in the herbal village. This positive response indicates that efforts to manage the herbal village have been successful in meeting the needs and expectations of the community. Community participation in the management of herbal villages is also considered good, and this is important to create an inclusive and sustainable environment. Recommendations from this study include improving accessibility and increasing community participation in decision-making processes. This research provides a deeper understanding of how green open space management can be carried out in a more responsive manner, focusing on community participation, and ensuring accessibility and availability of adequate facilities. The results of this study can be a guide for other green area managers to increase the responsiveness and quality of green open spaces in order to improve the welfare of society as a whole.